Pengaruh Iklan, Citra Merek, Dan Persepsi Harga Terhadap Keputusan Pembelian Produk Lipstik Wardah (Survei Pada Mahasiswa Manajemen Angkatan 2020 Universitas Bhayangkara Jakarta Raya) - Adinda Danty Pangestu; Dhian Tyas Untari; Andrian Andrian (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of advertisement, brand image and price perception on purchase decisions of Wardah lipstick products. This research uses a quantitative research. The sample in this study was 89 respondents using a saturated sampling technique with the criteria of 2020 management students from Bhayangkara Jakarta Raya University and had purchase Wardah lipstick products. The results of this study partially show that advertisement has a significant effect on purchase decisions. Brand image does not have a significant effect on purchase decisions. Price perception has a significant effect on purchase decisions. Simultaneously, advertisement, brand image and price perception have a significant effect on purchase decisions for Wardah lipstick products. The results of the adjusted r square test with a value of 73.6% where the independent variables in this study, namely advertisement, brand image and price perception together are able to influence purchase decisions for Wardah lipstick products.